Pengaruh Quick Ratio, Debt to Equity Ratio, Total Asset Turnover, Net Profit Margin terhadap Pertumbuhan Laba pada Perusahaan Property dan Real Estate Yang Terdaftar di BEI Tahun 2017-2019 - Siti Dini; Cindi Cenora Manalu; Desy Renica S Gultom; Lilis Suheri Purba (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This vstudy vintends vto vanalyze vand valso vassess vthe vimpact vof vthe vQuick vRatio, vDAR, vTATO, vand vNPM von vProfit vGrowth. vIn vthis vstudy, vthe vpopulation vused vis vProperty vand vReal vEstate vbusiness ventities vthat vwere vrecorded vin vthe v2017-2019 vperiod von vthe vIDX. vThis vstudy vuses vdata vanalysis vtechniques vsuch vas vMultiple vLinear vRegression, vDetermination vCoefficient vTest, vT-Test, vand vF vTest. vThe vresults vof vthe vassessment von vthis vresearch vtest vstate vthat vpartially vthe vQuick vRatio vhas va vnegative vand vsignificant vimpact von vProfit vGrowth, vPartially vthe vDAR vhas vno vimpact von vGrowth vProfit, vPartially vTATO vhas vno vimpact von vProfit vGrowth, vPartially vNPM vhas vno vimpact von vProfit vGrowth. vMeanwhile, vSimultaneously vQuick vRatio, vDAR, vTATO, vNPM vImpacted vProfit vGrowth vwith va vsignificant vvalue vof v0.049 vin vProperty vand vReal vEstate vCompanies vlisted vin vthe v2017-2019 vperiod von vthe vIDX. Keywords: vQuick vRatio, vDebt vTo vAsset vRatio, vTotal vAsset vTurn vOver, vNet vProfit vMargin, vProfit vGrowth.